The organization and implementation of community-based education programs for health worker training institutions in Uganda - Oria Hussein; Muhwezi Wilson; Nabirye Rose C; Okullo Isaac; Mbalinda Scovia N; Chang Larry W; Burnham Gilbert; Mwanika Andrew; Kaye Dan; Kijjambu Stephen; Atuyambe Lynn; Aryeija Warren (BMC, 2011)
Abstract Background Community-based education (CBE) is part of the training curriculum for most health workers in Uganda. Most programs have a stated purpose of strengthening clinical skills, medical knowledge, communication skills, community orientation of graduates, and encouragement of graduates to work in rural areas. This study was undertaken to assess the scope and nature of community-based education for various health worker cadres in Uganda. Methods Curricula and other materials on CBE programs in Uganda were reviewed to assess nature, purpose, intended outcomes and evaluation methods used by CBE programs. In-depth and key informant interviews were conducted with people involved in managing CBE in twenty-two selected training institutions, as well as stakeholders from the community, Ministry of Health, Ministry of Education, civil society organizations and local government. Visits were made to selected sites where CBE training was conducted to assess infrastructure and learning resources being provided. Results The CBE curriculum is implemented in the majority of health training institutions in Uganda. CBE is a core course in most health disciplines at various levels - certificate, diploma and degree and for a range of health professionals. The CBE curriculum is systematically planned and implemented with major similarities among institutions. Organization, delivery, managerial strategies, and evaluation methods are also largely similar. Strengths recognized included providing hands-on experience, knowledge and skills generation and the linking learners to the communities. Almost all CBE implementing institutions cited human resource, financial, and material constraints. Conclusions The CBE curriculum is a widely used instructional model in Uganda for providing trainee health workers with the knowledge and skills relevant to meet community needs. Strategies to improve curricula and implementation concerns need further development. It is still uncertain whether this approach is increasing the number graduates seeking careers in rural health service, one of the stated program goals, an outcome which requires further study.